Effects of moisture contents in soil and impulse polarity of earth electrode under high impulse conditions - Ahmad, Hussein; Idris, N. A.; Mohamad Nor, N. (2006)
The study on the physics of discharges in soil and performance of earthing networks subjected and obtain better electrical models of earthing systems. In this study, the characteristics of medium grain size sand of different moisture contents and impulse polarity are investigated. The soil characteristics of various moisture contents under high impulse currents have been well studied in previous work. Until today, no publication has been made on the dry soil characteristics and no direct comparisons has been made between the characteristics of dry and wet soils under impulse conditions. This paper is therefore aimed to observe the characteristics of dry and wet soil under both impulse polarities. The results were discussed based on its voltage and current traces, impulse resistances and breakdown characteristics of the cylindrical test cell.